Transforming Digital Curriculum Management through the Integration of Interactive Digital Boards in Advanced Classes - Nita Nasehat Nur Arini; Ahmad Azkal Azkiya (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This research aims to analyze the transformation of digital curriculum management through the integration of Interactive Digital Boards in advanced classes. The research focus is directed toward changes in the curriculum planning process, the efficiency of managing learning documents, the improvement of teachers' digital competence, and its implications for teaching practices. which includes data reduction, data presentation, and continuous conclusion drawing. This study involved three key informants, consisting of a vice principal for curriculum, a curriculum coordinator, and advanced class teachers. Data were collected through semi-structured interviews, classroom observations, and document analysis. The analyzed documents included lesson plans, syllabi, curriculum guidelines, and school policy documents related to digital learning implementation. Data analysis was conducted using the interactive model of Miles and Huberman, which involves data reduction, data display, and conclusion drawing. The research findings indicate that the integration of promotes a shift in curriculum management from a static administrative system toward a more flexible, adaptive, and collaborative system. The use of has been proven to improve the efficiency of curriculum document management, save up to 40% of lesson preparation time, and strengthen teachers' digital competence and confidence. This research provides a theoretical contribution to the development of digital curriculum management studies and a practical contribution as a reference for schools in optimizing interactive technology as part of a sustainable curriculum management system.